Macrofungal diversity of the Gireniz Valley (Denizli, Turkey) - Kaygusuz, Oğuzhan; Gezer, Kutret (Biodiversity: Research and Conservation, 2016)
This study was conducted to determine the macrofungal diversity of the Gireniz Valley. From 2010 to 2013, 674 samples of macrofungi were collected during field surveys conducted periodically in appropriate ecological conditions. As a result of macroscopic and microscopic studies, a total of 114 macrofungal taxa from the classes Pezizomycetes, Agaricomycetes and Tremellomycetes, distributed in 12 orders and 39 families, were determined. Five families, 10 genera and 20 taxa belonging to one order of Pezizomycetes class, 33 families, 57 genera and 93 taxa belonging to 10 orders of Agaricomycetes class and one family, one genus and one taxon belonging to one order of the class Tremellomycetes were identified. It was determined that among 114 macrofungal taxa identified in the study area, 45 were edible, 60 inedible, and nine were poisonous.